The effect of heat input on the microstructure and mechanical properties of 7075-T6 ultra-high strength aluminum alloy weld by laser wire filling welding - Wenqiang GAO; Fei XU; Xuyi MA; Luyun GUO; Yiting LU (Hanjie xuebao, 2025)
High quality connection of 2.0 mm thick 7075-T6 ultra-high strength aluminum alloy was achieved using laser wire filling welding, and the effect of heat input on the microstructure and mechanical properties of ultra-high strength aluminum alloy welds was studied. The microstructure of the 7075-T6 aluminum alloy weld by laser wire filling welding was a typical cast structure. The central area of the weld was a relatively large equiaxed dendritic structure with no obvious texture, and the strengthening phase particles in the weld could not be fully precipitated, resulting in a certain degree of decrease in joint strength. With the increase of heat input, the melting zone and melting width of the weld cross-section gradually increased, while the microstructure and texture characteristics of equiaxed dendrites at the center of the weld did not show significant changes. The grain size of the central area of the weld first rapidly increased and then slowly increased. The microhardness distribution of joints under different heat input conditions was basically the same, and the areas with the most severe softening were all in the weld zone. With the increase of heat input, the tensile strength of joints firstly increased and then decreased. By regulating the heat input of laser wire filling welding, the strength coefficient of 7075 aluminum alloy joints could reach 74.9%.